BAHASA PASER DI KALIMANTAN KAJIAN LINGUISTIK DIAKRONIS - Nurul Fazriani; Inyo Yos Fernandez; Wakit Abdullah (PRASASTI: Journal of Linguistics, 2016)
This research conducts to study and to clarify the status of PSR language in East Kalimantan using a comparative historical linguistics. Linguists have radically different opinion in defining the status of PSR language; Hudson (1967) classified PSR language into Barito Timur Laut language family, Riwut (1961) classified PSR language into Dayak Ngaju language family, while Wurm & Shiro (1983) dan Cense & Uhlenbeck (1958) classified PSR language into Melayu language family.This research used mixed method between quantitative and qualitative. The instrument of this this research were Swadesh as a primary instrument and Notehofer vocabulary as a complementary instrument. The data analysis was done by comparing PSR language to LWG language from Dayak language family and BJR language from Melayu language family covering phonological and lexical aspects.The result of the synchronic study shows several things on the phonological aspect. First, PSR and LWG language have similarity in the distribution of vocal phoneme of /o/ and consonant phoneme of /q/ which are not found in BJR language that merely has high vocal of /i/ and /u/ and low vocal of /a/. Second, PSR and LWG language have similarity in the distribution of /e/ ph oneme which is not distributing in the last position. Third, PSR and LWG language don’t have consonant phoneme of /h/ which is found in BJR language. Fourth, PSR language does not have diphthong of ew/ and /Əw/ which are found in LWG and BJR languages.The result of the diachronic study obtained from quantitative and qualitative analysis. From the quantitative analysis using lexicostatistics technique, presentation of historical relationship among languages were obtained; PSR-LWG by 51%, PSR-BJR 24%, and LWG-BJR 12%. In the qualitative analysis, it is found that the correspondence of the phoneme is regular. Phonemes of /e/, /o/, /l/, /c/ PSR language corresponds respectively to the phonemes of /i/, /ə/, /e/, /r/, /s/ in the position of ultima, penultimate and prapenultima on LWG language. Furthermore, based on a joint lexical innovation that occurs in the PSR and LWG languages, there are a number of lexical data found which shows similarities in both languages. Keywords: Paser Language, Sinchronic, Diachronic, Quantitative, Qualitative,                      Lexicostatistics, Reconstruction